The Admissibility of "Acquittal Evidence" in Criminal Trials: Toward Reform - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2003)
Recent case law at appellate level in a number of common law jurisdictions has considered the admissibility of "acquittal evidence" – meaning, in the context of this article, either evidence of a defendant's earlier acquittals or evidence on which the acquittals were based. The author argues that the various rulings have resulted in uncertainty and inconsistency and illustrate the difficulty of establishing a single admissibility rule. After analysing the New Zealand case law, the author examines the relevant sections in the proposed Evidence Code, published by the New Zealand Law Commission in 1999, and she concludes by exploring some alternative legislative and judicial resolution of the issues.